2023
DOI: 10.1158/1538-7445.agca22-pr009
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PR009: Revisiting the bad luck hypothesis: Cancer risk and aging are linked to replication-driven changes to the epigenome

Abstract: Aging is the leading risk factor for cancer. While some have proposed that the age-related accumulation of somatic mutations drives this relationship, it is likely not the full story. Here, we show that both aging and cancer share a common epigenetic replication signature, which we modeled from DNA methylation data in extensively passaged immortalized human cells in vitro and tested on clinical tissues. This epigenetic signature of replication – termed CellDRIFT – increased with age across multiple tissues, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Strikingly, we also found long-lived beta cells in the HFD setting, thus indicating that some beta cells do not proliferate during long periods of hyperglycemia in vivo. Previous studies have shown that proliferation promotes an immature and less functional beta cell phenotype than non-proliferating beta cells 83 , which is also supported by the higher levels of beta cell identity and function markers in CR islets. Importantly, this largely post-mitotic state of CR beta cells could also explain the reduced accumulation of DNA damage, as cell proliferation triggers higher accumulation of genetic mutations and replication-dependent stress that can lead to disease and aging 84 .…”
Section: Discussionmentioning
confidence: 62%
“…Strikingly, we also found long-lived beta cells in the HFD setting, thus indicating that some beta cells do not proliferate during long periods of hyperglycemia in vivo. Previous studies have shown that proliferation promotes an immature and less functional beta cell phenotype than non-proliferating beta cells 83 , which is also supported by the higher levels of beta cell identity and function markers in CR islets. Importantly, this largely post-mitotic state of CR beta cells could also explain the reduced accumulation of DNA damage, as cell proliferation triggers higher accumulation of genetic mutations and replication-dependent stress that can lead to disease and aging 84 .…”
Section: Discussionmentioning
confidence: 62%
“…In addition to studying the role that telomeres play in aging, cell models have been used to show and characterize cellular senescence, oxidative stress, mitochondrial dysfunction, and protein homeostasis (Bodnar et al 1998;Gerasymchuk et al 2022; C. J. Minteer et al 2023;Parrinello et al 2003). Once it was shown that methylation aging signatures tracked well across tissues and species, it was next on the docket to determine how well the .…”
Section: Introductionmentioning
confidence: 99%
“…(Campisi 2013; C. J. Minteer et al 2023). Overall, it has been taken to suggest that tissues prone to faster epigenetic aging may also be primed for tumorigenesis, which is further supported by the observation of accelerated epigenetic aging in normal adjacent breast tissue from women with breast cancer, relative to controls.…”
Section: Introductionmentioning
confidence: 99%

The Latent Aging of Cells

Niimi,
Gould,
Thrush-Evensen
et al. 2024
Preprint
“…Among the potential molecular alterations that could be used to measure mitotic age, somatic mutations and DNA methylation (DNAm) have emerged as the most promising ones 11,14,15,23 . DNAm-based mitotic-like counters hypothesized to track the cumulative number of DNA methylation errors arising during cell division in both stem-cell and expanding progenitor cell populations have been proposed [16][17][18][24][25][26][27][28][29] , yet confounders such as cell-type heterogeneity (CTH) 30 and chronological age 24 have cast doubt on the biological and clinical significance of these counters and their total mitotic age estimates (defined here as the cumulative number of divisions in both stem-cells and amplifying progenitor populations). Moreover, DNAm changes in normal and preneoplastic lesions often display a stochastic pattern 19,31,32 , which can pose specific statistical challenges to estimating mitotic age.…”
mentioning
confidence: 99%